A Preliminary Experimental Investigation of Wet Fine Erosion in Two-Phase Flow - Ya, H.H. (Institute of Physics Publishing, 2018)
Solid particles below 62 μm is classified as fine. In oil producing operation, the most commonly used downhole sand screen can only capture solid particles of 140 μm and above. Most predictive erosion model is limited to particle size of 100 μm with single phase flow assumption because it is commonly believed that erosion due to particles below 100 μm is insignificant and typically ignored by oil and gas consultants when proposing facilities design. The objective of this paper is to investigate the impact of fines particle on mild steel plate in two-phase flow at different collision angles. A two phase flow loop was set up. The average size of fine particle was 60 μm, mixed with water with sand to water ratio at 1:65 wt/wt. The mild steel plates were oriented at three different impact angles which are -30°, 30° and 90°, with respect to the horizon. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), surface roughness and Vickers micro hardness techniques were used to quantify the effects of fine particle on the exposed surface. © Published under licence by IOP Publishing Ltd.